Participation rate in cervical cancer screening in general practice related to the proximity of gynecology care facilities: A 3 year follow-up cohort study - Quersin, François; Serman, Fanny; Favre, Jonathan; Rochoy, Michaël; Descamps, Axel; Gers, Elise; Duhamel, Alain; Collins, Claire; Deken-Delannoy, Valérie; Berkhout, Christophe; Raginel, Thibaut (Frontiers in Public Health, 2022)
Cervical cancer screening (CCS) by Pap tests is mainly performed by gynecologists in France, but also by general practitioners (GPs) and midwives. The screening uptake is insufficient to reduce the incidence of cervical neoplasms. Our aim was to investigate the association between screening rates in patients listed with GPs and the distance between GPs' offices and gynecology facilities. The population of 345 GPs, and their 93,918 female patients eligible for screening over 3 years (2013–2015), were derived from the Health Insurance claim database. We estimated the socioeconomic level of the geographical area of GPs' offices using the European Deprivation Index (EDI). The proximity of gynecology facilities was calculated by computing their distance from GPs' offices (in order to adjust the proximity of gynecology facilities with EDI and performance of smears by the GP). The number of gynecologists within 5 km of a GP's office was associated with the CCS rate increasing by 0.31% for every unit increase in the density of gynecologists within 5 km (p < 0.0001). The close proximity of gynecology facilities was not significantly associated with screening uptake among female patients when the office of the GP where they were registered was settled in a deprived area.